Lippincott's clinical skills series medication basic set - Conaway, Deborah Jean; Studio Three Productions (Philadelphia : Lippincott- Raven, 1996)
This video series offers essentisl guidence and detailed, up-closed demotrations of clinical skill used by nurse and other health care providers.
Videocassettes is available at Koleksi Media Perpustakaan HUKM
j.1-Understanding medical guidlines; j.2-Administering oral and inhalation medications; j.3-Administering injectable medications; j.4-Administering topical medications
Technical consultant, Deborah Jean Conaway
Keywords: Drugs -- administration and dosage -- videocassettes; Nursing -- videocassettes; Drug Therapy -- nursing -- videocassettes; Administration, Tropical -- videocassettes